Fenomena Peralihan Bank Konvensional ke Bank Syariah di Aceh - Muklir Muklir; Syamsudin Syamsudin; Muhammad Gusti; Abdul Aziz (Sociology Department Of Syiah Kuala University, 2022)
Islamic financial institutions aim to improve the economic empowerment of the people of Aceh based on the principles of Islamic economics (sharia). This article aims to describe the phenomenon of switching from conventional banks to Islamic Sharia banks as a form of implementation of Aceh Qanun Number 11 of 2018 concerning Islamic Financial Institutions. This study uses a qualitative approach. Data collection techniques using observation and interviews The data obtained were analyzed using qualitative descriptive techniques. The results showed that the transition of conventional banks to Islamic banks as a form of Qanun LKS implementation has still not been effective and efficient, so customers and business actors still do not significantly feel the impact. The transition of conventional banks to Islamic banks as a form of implementation of Qanun LKS also shows unpreparedness in terms of systems, programs, and services. This had an impact on the service provided to bank customersAbstrakLembaga Keuangan Syariah bertujuan meningkatkan pemberdayaan ekonomi masyarakat Aceh berdasarkan prinsip ekonomi Islam. Artikel ini bertujuan untuk mendeskripsikan tentang fenomena peralihan Bank Konvensional ke Bank Syariah sebagai bentuk implementasi Qanun Aceh Nomor 11 tahun 2018 tentang Lembaga Keuangan Syariah. Kajian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data menggunakan observasi dan wawancara. Data yang diperoleh kemudian dianalisis menggunakan teknik deskriptif kualitatif. Hasil penelitian menunjukkan bahwa Peralihan Bank konvensional ke bank syariah sebagai bentuk implementasi Qanun LKS belum berjalan efektif dan efisien sehingga dampaknya pun masih belum dapat dirasakan secara signifikan, baik oleh nasabah maupun pelaku usaha. Peralihan Bank Konvensional ke Bank Syariah sebagai bentuk implementasi Qanun LKS juga masih menunjukkan ketidaksiapan dalam hal sistem, program, serta pelayanan. Hal ini mengakibatkan rendahnya pelayanan kepada nasabah.